PRODUÇÃO DE CAROTENOIDES POR RHODOTORULA GLUTINIS ATRAVÉS DE CULTIVO SUBMERSO – UMA REVISÃO INTEGRATIVA - DIAS, TALITA ARAÚJO (2021)
The carotenoids are a large group of pigments present in nature, identified in photosynthesizing and non-photosynthesizing organisms. They are normally used commercially as food coloring and in nutritional supplements, being precursors of vitamin A, acting as antioxidants and regulators of the immune system response. The production of carotenoids occurs by several microorganisms including: Rhodotorula, Phaffia rhodozyma, Sporobolomyces, Blakeslea trispora, Dunaliella salina and Haematococcus pluvialis, among these carotenoid producers the genus Rhodotorula stands out for being widely distributed in nature and for having the ability to biosynthesize different carotenoids and for its ability to use low cost substrates. These advantages have been drawing much attention from industries, since the potential for growth in low-cost substrates can lead to the use of agroindustrial waste, becoming a viable alternative to reuse. Thus, this work aimed to survey the literature on the production process of carotenoids by the yeast Rhodotorula glutinis. The following keywords were used to search the databases: Carotenoids; Submerged Culture; Rhodotorula glutinis; Yeast; Carotenoid Properties. The database used was WebofScience in addition to commercial search articles on the google platform. The studies showed that regardless of the culture medium used, the optimal conditions obtained for cultivation were: temperature 27°C, 250 rpm agitation and pH 7. Furthermore, they showed that the variables alone have less influence than when observed together.